USING ROLE-PLAY ACTIVITIES TO MOTIVATE STUDENTS TO SPEAK ENGLISH - Mavlanova O.SH.,Jurayeva Sevinch Shovkat qizi (International Journal of Literature and Language Studies, 2026)
Introduction. Speaking skill is considered one of the most important components of foreign language learning because it allows learners to communicate ideas, emotions, and information effectively. In modern English language teaching, developing speaking ability has become a major educational objective, particularly in communicative language classrooms where interaction and active participation are emphasized. However, many students experience difficulties in speaking English due to lack of confidence, fear of making mistakes, limited vocabulary, and insufficient opportunities for real communication. As a result, teachers are required to apply interactive and motivating teaching methods that encourage students to participate actively in oral communication. One of the most effective methods for improving speaking motivation is the use of role-play activities. Role-play refers to classroom activities in which students act out real-life situations by taking different social roles and communicating with one another in English. This method creates a communicative environment that helps learners practice language naturally and meaningfully. Unlike traditional teacher-centered approaches, role-play activities increase student interaction, creativity, and emotional involvement in the learning process. The use of role-play activities is especially important because it reduces students’ anxiety and helps them overcome psychological barriers related to speaking English. Through role-play, learners can simulate everyday communicative situations such as shopping, traveling, visiting a doctor, or participating in job interviews. These practical experiences improve not only linguistic competence but also communicative confidence and fluency. Furthermore, role-play supports the development of pronunciation, vocabulary usage, listening comprehension, and spontaneous speech production. This study aims to investigate the effectiveness of role-play activities in motivating students to speak English and improving their communicative abilities. Special attention is given to the pedagogical advantages of role-play, student participation, and classroom interaction in English language learning.